Quality of life and epilepsy surgery in childhood and adolescence - Isabella C. Gagliardi; Catarina A. Guimarães; Elisabete A.P. Souza; Kátia M.R. Schmutzler; Marilisa M. Guerreiro (Arquivos de Neuro-Psiquiatria)
Epilepsy can affect the quality of life (QOL) of patients. The temporal lobe epilepsy (TLE) is often refractory to medication, which has an adverse impact on QOL. The surgery can be a form to control the seizures and to improve the QOL of the patients. OBJECTIVE: The aim of this study was to verify the QOL of children and adolescents with TLE who underwent surgery for epilepsy, comparing QOL before and after surgery and investigating which parameters showed improvement. METHOD: We used semi-structured questionnaire in the pre-and post-surgery in 13 patients. The data were analyzed using the Wilcoxon test. RESULTS: The analysis showed that there was general improvement in the QOL postoperatively. There was improvement in general health issues, adverse effects of antiepileptic drugs and the relationship with parents. CONCLUSION: When properly indicated, epilepsy surgery improves quality of life of patients with TLE.